Adolescent substance dependency in relation to parental substance (ab)use - Rus-Makovec, Maja (Zdravstveno varstvo, 2010)
Problem: Relations between adolescents'' substance dependency status (yes-no) as independent and adolescent self and family evaluations and parental indicators of substance dependency as dependent variables were studied. Methods: All together 197 families were included (father, mother, adolescent -mean age of adolescent was 17.2 years). Rosenberg self - esteem scale, originally constructed semantic differential perceived family climate, Zung depression scale and SASSI-3 (Substance Abuse Subtle Screening Inventory) instrument were applied. Multivariate and univariate approach were applied to verify hypotheses about differences in dependent variables regarding the independent one also with estimated mothers'' and fathers'' dependency as two covariates. Results: Level of depression was significantly higher, but level of self-esteem and family climate evaluation were significantly lower in dependent adolescents. Fathers of non-dependent adolescents and mothers of dependent adolescents were found more substance dependency vulnerable. Adolescent dependence status differed more frequently in fathers'' than in mothers'' SASSI-3 sub scores. Conclusions: Results indicate that in group of substance dependent adolescent families with healthier and more engaged fathers participated in the study. Support for mothers'' vulnerability and need for fathers'' involvement in treatment of dependent adolescent is underlined.
Keywords: depresija (medicina); družinsko vzdušje; mladostniki; psihotropne snovi; samospoštovanje; starši; zloraba